Access networks 5th International ICST Conference on Access Networks, AccessNets 2010 and First ICST International Workshop on Autonomic Networking and Self-Management in Access Networks, SELFMAGICNETS 2010, Budapest, Hungary, November 3-5, 2010, Revised Selected Papers - Szabó, Róber; Zhu, Hua; Imre, Sándor; Chaparadza, Ranganai (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2011)
This book constitutes the reviewed post-proceedings of the 5th International ICST Conference on Access Networks, AccessNets 2010, and of the satellite event , the First International ICST Workshop on Autonomic Networking and Self-Management in Access Networks, SELFMAGICNETS 2010, held jointly in Budapest, Hungary in November 2010. The 19 revised full papers presented together with one invited paper and four poster papers were carefully reviewed and selected for inclusion in the proceedings. The papers are organized in topical sections on next generation wireless networks, emerging applications, next-generation broadband networks and autonomic networking and network self-management.